2021
DOI: 10.1177/2192568221994794
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Assessment of Postoperative Paraspinal Muscle Changes After Lumbar Interbody Fusion With or Without Minimally Invasive Techniques

Abstract: Study Design: Retrospective cohort study. Background: Percutaneous pedicle screws (PPS) have the advantage of being able to better preserve the paraspinal muscles when compared with a traditional open approach. However, the nature of changes in postoperative paraspinal muscle after damage by lumbar fusion surgery has remained largely unknown. It is clinically important to clarify and compare changes in paraspinal muscles after the various surgeries. Objective: (1) To determine postoperative changes of muscle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…However, at 6 months after surgery, there was no signi cant difference in the FI rate or muscle density between the two groups. Although it is not clear how long it takes from paraspinal muscle injury until there is detectable FI, some studies have shown that 12 months after surgery is a reasonable time to evaluate postoperative FI [29,30]. He et al believe that there exists a mutual effect between paraspinal muscle FI and muscle atrophy [31], and we speculate that there will be a difference in the paraspinal muscle area between the two groups after long-term follow-up.…”
Section: Discussionmentioning
confidence: 72%
“…However, at 6 months after surgery, there was no signi cant difference in the FI rate or muscle density between the two groups. Although it is not clear how long it takes from paraspinal muscle injury until there is detectable FI, some studies have shown that 12 months after surgery is a reasonable time to evaluate postoperative FI [29,30]. He et al believe that there exists a mutual effect between paraspinal muscle FI and muscle atrophy [31], and we speculate that there will be a difference in the paraspinal muscle area between the two groups after long-term follow-up.…”
Section: Discussionmentioning
confidence: 72%
“…In order to evaluate the changes of MF after PE-TLIF, we compared the FCSA and FI rate of MF at pre-operation, 12-month follow-up, 24-month follow-up, and at final follow-up. Some studies have shown that the decrease of muscle volume and the increase of fat deposition are the main characteristics of paraspinal muscle degeneration ( 23 , 24 ). Kang et al confirmed by MRI that the degree of paraspinal muscle degeneration can be reflected by the decrease of paraspinal muscle FCSA and FI ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increase in fatty infiltration is reflected by a decrease in mean density (Hounsfield units (HU)) [ 15 ] (Table 1 summarizes the pathological manifestations and corresponding imaging features of the paraspinal muscle and fat). Kameyama, et al [ 16 ] showed a significant correlation between the fat infiltration rate assessed using MRI and muscle density assessed using CT, and both showed a significant correlation in the assessment of the CSA of the paraspinal muscles. CT is easier to use in the clinical setting because of its simplicity and reproducibility (Fig.…”
Section: Spine Imaging Technologymentioning
confidence: 99%
“… Kameyama et al 16 ] applied the summary method, as proposed by previous authors, to measure the cross-sectional area and muscle density on CT axial images of the paraspinal muscles. A: multifidus; B: erector spinae; C: lumbaris major.…”
Section: Spine Imaging Technologymentioning
confidence: 99%